Lattice Boltzmann method and immersed boundary method for the simulation of viscous fluid flows - Falagkaris, Emmanouil (The University of Edinburgh, 2018)
Most realistic fluid flow problems are characterised by high Reynolds numbers and complex boundaries. Over the last ten years, immersed boundary methods (IBM) that are able to cope with realistic geometries have been applied to Lattice- Boltzmann methods (LBM). These methods, however, have normally been applied to low Reynolds number problems. In the present work, an iterative direct forcing IBM has been successfully coupled with a multi-domain cascaded LBM in order to investigate viscous flows around rigid, moving and wilfully deformed boundaries at a wide range of Reynolds numbers. The iterative force-correction immersed boundary method of (Zhang et al., 2016) has been selected due to the improved accuracy of the computation, while the cascaded LB formulation is used due to its superior stability at high Reynolds numbers. The coupling is shown to improve both the stability and numerical accuracy of the solution. The resulting solver has been applied to viscous flow (up to a Reynolds number of 100000) passed a NACA-0012 airfoil at a 10 degree angle of attack. Good agreement with results obtained using a body-fitted Navier-Stokes solver has been obtained. At moving or deformable boundary applications, emphasis should be given on the influence of the internal mass on the computation of the aerodynamic forces, focusing on deforming boundary motions where the rigid body approximation is no longer valid. Both the rigid body and the internal Lagrangian points approximations are examined. The resulting solver has been applied to viscous flows around an in-line oscillating cylinder, a pitching foil, a plunging SD7003 airfoil and a plunging and flapping NACA-0014 airfoil. Good agreement with experimental results and other numerical schemes has been obtained. It is shown that the internal Lagrangian points approximation accurately captures the internal mass effects in linear and angular motions, as well as in deforming motions, at Reynolds numbers up to 4 • 104. Finally, an expanded higher-order immersed boundary method which addresses two major drawbacks of the conventional IBM will be presented. First, an expanded velocity profile scheme has been developed, in order to compensate for the discontinuities caused by the gradient of the velocity across the boundary. Second, a numerical method derived from the Navier-Stokes equations in order to correct the pressure distribution across the boundary has been examined. The resulting hybrid solver has been applied to viscous flows around stationary and oscillating cylinders and examined the hovering flight of elliptical wings at low Reynolds numbers. It is shown that the proposed scheme smoothly expands the velocity profile across the boundary and increases the accuracy of the immersed boundary method. In addition, the pressure correction algorithm correctly expands the pressure profile across the boundary leading to very accurate pressure coefficient values along the boundary surface. The proposed numerical schemes are shown to be very efficient in terms of computational cost. The majority of the presented results are obtained within a few hours of CPU time on a 2.8 GHz Intel Core i7 MacBook Pro computer with a 16GB memory.
Keywords: aerodynamic behaviour of immersed bodies; flow characteristics; immersed boundary methods; Lattice- Boltzmann methods; iterative force-correction immersed boundary method